2011
DOI: 10.1021/ef1012209
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron Radiation Studies of Additives in Combustion, II: Soot Agglomerate Microstructure Change by Alkali and Alkaline-Earth Metal Addition to a Partially Premixed Flame

Abstract: International audienceSmall-angle X-ray scattering (SAXS) has been used in a comparative study to characterize soot particle formation in a partially premixed ethylene−air flame into which plain water, and 0.1 mol/L solutions of potassium chloride, cesium chloride, barium chloride, and calcium chloride were aspirated. The plain water results are assumed to be the reference in this study. On the basis of previous findings, a two-level universal fitting function for the scattering intensity I(q), 0.04 nm−1 < q <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Corannulene has been found to be present in flames (Lafleur et al, 1993), however its clustering effectiveness is expected to be less significant than those for larger curved molecules prevalent in sooting environments due to its weaker interaction energy. Potassium is readily ionised in a flame and has been shown to impact soot nucleation through the production of higher particle numbers and smaller particle sizes (Haynes et al, 1979;Di Stasio et al, 2011;Simonsson et al, 2017). Due to this known influence and the straightforward incorporation of the spherical potassium cation within an atomic model, K + provides a representative cation useful for exploring the interactions of cPAHs and ions in a large dynamic system.…”
Section: Nucleation Simulationsmentioning
confidence: 99%
“…Corannulene has been found to be present in flames (Lafleur et al, 1993), however its clustering effectiveness is expected to be less significant than those for larger curved molecules prevalent in sooting environments due to its weaker interaction energy. Potassium is readily ionised in a flame and has been shown to impact soot nucleation through the production of higher particle numbers and smaller particle sizes (Haynes et al, 1979;Di Stasio et al, 2011;Simonsson et al, 2017). Due to this known influence and the straightforward incorporation of the spherical potassium cation within an atomic model, K + provides a representative cation useful for exploring the interactions of cPAHs and ions in a large dynamic system.…”
Section: Nucleation Simulationsmentioning
confidence: 99%
“…13 The concentration of ions in a flame can be artificially increased through the addition of alkali and other metals, which easily ionize at flame temperatures. Electron microscopy 15 and small angle X-ray diffraction 16 revealed that primary particles increased in number and decreased in size with these metal additives, with significant reductions in the mass of particulates produced (50-90% reduction being reported for polystyrene combustion 17 ).…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, the same as soot, the physical and chemical changes of gasified metal also occur near coal particles [25]. In the study of hydrocarbon flame and diesel engines, it is found that gaseous metals can affect the formation of soot and tar [26,27]. Therefore, these gasified metals, especially alkali metals and alkaline earth metals, may also affect the sooting process of coal tar.…”
Section: Introductionmentioning
confidence: 99%